Evaluasi Konsep Ramah Anak berdasarkan Teori Gestalt pada Tekstur Desain Fungsi Ruang di Lingkungan Ruang Dalam Hunian Vertikal (Studi Kasus Rumah Susun di Kota Kendari) - Rafi, Abdur; Eni, Sri Pare; Pasaribu, Ramos P. (Sultra Civil Engineering Journal (SCiEJ), 2025)
This study evaluates the extent to which child-friendly concepts in apartments in Kendari City have integrated Gestalt principles into the texture and function of spaces. This study used a qualitative approach with descriptive-analytical methods to gain a deeper understanding of the application of child-friendly concepts in vertical housing. This research was conducted in several apartments in Kendari City: Ponggolaka Apartments, PPS Apartments, Puday Apartments, and Bungkutoko Apartments. Based on the research results and discussion, it can be concluded that the application of texture in the spatial design of apartments in Kendari City has not fully met the basic principles of visual and tactile perception that support child comfort and development: Proximity, Similarity, Continuity, Closure, Figure-Ground, Visual Texture Variation, Tactile Texture (touch), Regularity and Balance, Textural Scale and Proportion, and Sensory Stimulation Function.